Statistical analysis of the use of digital technologies in organizations: regional aspect - V. G. Minashkin; P. E. Prokhorov (Статистика и экономика, 2018)
Purpose of the study. The digitization of the economy transforms the ways of delivering and consuming goods and services, which in turn affects all spheres of human activity. The field of electronic commerce is a relatively young area of statistical observation, therefore, at present, researchers, government officials, business representatives and other interested persons lack statistical information, which, in turn, helps to study the economic, social and environmental consequences of the digitized world. The purpose of this study is a quantitative description of the development trends and the degree of regional differentiation of electronic commerce in the Russian Federation in the context of international comparisons.Materials and methods. The article used the official statistical information of Rosstat and Eurostat, on the basis of which the trends in the development of electronic interaction in the business sphere were analyzed and tools were proposed for a quantitative description of regional digital gaps in the regions of Russia and the European Union countries for 2010–2017. As quantitative characteristics of regional differentiation, statistical indicators of variation and localization indicators were used (based on Gini and Lorentz coefficients). Results. The analysis conducted in the study showed the consistency of assessments of the regional digital divide based on economic and statistical indicators. This approach expands the possibilities for an in-depth quantitative description of the processes occurring in the field of digital trading. In addition, it was possible to identify the level of development of e-commerce in Russia in comparison with the leading economies of the European Union, as well as identify the scale of penetration of broadband Internet access among organizations, the involvement of Russian regions and European countries in the processes of placing and receiving orders for goods and services in the global network. According to the results of the study, it should be concluded that despite the obvious leading position of some European countries not only in comparison with Russian regions, but also on a global scale, the development of e-commerce in Russia and the European Union occurs at a comparable pace. It should also be noted that in the case of Russia, this development is more homogeneous in terms of regional differentiation.Conclusion. Despite the fact that digitalization is transforming both business and personal life, there is currently an extremely small amount of information that helps quantify the economic, social and environmental consequences of this phenomenon. In order to further improve the statistical accounting of the digital economy in general and aspects of electronic commerce in particular, at this stage it is necessary: to determine the nature, structure, characteristics, elements, levels of control, movement of the digital economy’s commodity money supply for statistical purposes; identify specific digital technologies, their use in sectors of the economy and their contribution to the gross domestic product; develop a system of statistical indicators on the basis of state programs and strategies, the current methodology of statistical accounting of the information society, international recommendations and development of quantitative measurement of non-governmental organizations.